Distinct expression of select and transcriptome-wide isolated 3'UTRs suggests critical roles in development and transition states. - Shaoyi Ji; Ze Yang; Leonardi Gozali; Thomas Kenney; Arif Kocabas; Carolyn Jinsook Park; Mary Hynes (PLoS ONE)
Mature mRNA molecules are expected to be comprised of a 5'UTR, a 3'UTR and a coding region (CDS). Unexpectedly, however, there have been multiple recent reports of widespread differential expression of mRNA 3'UTRs and their cognate coding regions (CDS), reflecting the expression of isolated 3'UTRs (i3'UTRs); these i3'UTRs can be highly expressed, often in reciprocal patterns to their cognate CDS. As with other long non-coding (lncRNAs), isolated 3'UTRs are likely to play an important role in gene regulation, but little is known about the contexts in which they are deployed. To illuminate the functions of i3'UTRs, here we carry out in vitro, in vivo and in silico analyses of differential 3'UTR/CDS mRNA ratio usage across tissues, development and cell state changes both for a select list of developmentally important genes as well as by unbiased transcriptome-wide analyses. Across two developmental paradigms we find a distinct switch from high i3'UTR expression for stem cell related genes in proliferating cells to high CDS for these genes in newly differentiated cells. Unbiased transcriptome analysis across multiple gene sets shows that regardless of tissue, genes with high 3'UTR to CDS ratios belong predominantly to gene ontology categories related to cell-type specific functions. In contrast, the gene ontology categories of genes with low 3'UTR to CDS ratios are similar across tissues and relate to common cellular functions. We further show that, at least for some genes, traditional transcriptional start site genomic elements correspond to identified RNAseq 3'UTR peak regions, suggesting that some i3'UTRs may be generated by de novo transcription. Our results provide critical information from which detailed hypotheses for individual i3'UTRs can be tested, with a common theme that i3'UTRs appear poised to regulate cell-specific gene expression and state.